Coherent cyclotron emission with a helical wavefront from multi-electron system accelerated by the circularly polarized wave - Yuki Goto; Shin Kubo; Toru Ii Tsujimura (New Journal of Physics, 2021)
In this study, we calculated coherent electron cyclotron emission (ECE) with helical wavefront from a multi-electron system which passes through a magnetic mirror field with cyclotron motion. ECE from a multi-electron system is usually incoherent radiation due to the random rotation phase of each electron, and it is difficult to observe the helical wavefront. However, when a resonant external electromagnetic field is applied, the gyro-phase of electrons are controlled, and coherent ECE is expected to be observed. These processes were numerically calculated under the given experimental condition and confirmed that the higher harmonics ECE has helical wavefront.